Quantification of deformation induced α'-martensite in Fe–19Cr–3Mn–4Ni–0.15C–0.15N austenitic steel by in situ magnetic measurements. (September 2015) - Hauser, M.; Wendler, M.; Ghosh Chowdhury, S.; Weiß, A.; Mola, J.
Abstract : An in situ magnetic device was employed to quantify the deformation induced martensite in a Fe–19Cr–3Mn–4Ni–0.15C–0.15N (wt-%) steel during tensile testing in the temperature range of −40 to 22°C. The new device consists of an electromagnetic field which serves to magnetise the martensite phase as it forms during tensile loading and a second coil to detect the effective electrical potential difference induced by the magnetisation of tensile specimens. To implement the in situ measurement system, a correlation was necessary between the induced electrical potential difference and the deformation induced martensite fractions during uniaxial static tensile tests. The correlation procedure was found to require only the quantification of deformation induced martensite content in a tensile specimen strained until fracture using an ex situ magnetic saturation unit.